Epigenetic regulation in tomato fruit ripening - Ming, Yucheng; Jiang, Libo; Ji, Dongchao (Frontiers in Plant Science, 2023)
Fruit ripening is a crucial stage in quality development, influenced by a diverse array of internal and external factors. Among these factors, epigenetic regulation holds significant importance and has garnered substantial research attention in recent years. Here, this review aims to discuss the breakthrough in epigenetic regulation of tomato (Solanum lycopersicum) fruit ripening, including DNA methylation, N6-Methyladenosine mRNA modification, histone demethylation/deacetylation, and non-coding RNA. Through this brief review, we seek to enhance our understanding of the regulatory mechanisms governing tomato fruit ripening, while providing fresh insights for the precise modulation of these mechanisms.